Strategic Effects of Supply Chain Inventories on Sales Performance. Issue 2 (3rd April 2021) - Kim, Sunghak; Na, Jaeseog; Kim, Bowon
Abstract: This paper examines the non-linear relationship between a firm's inventory and sales performance. Specifically, whether there exists an optimal level of inventory that maximizes sales performance is investigated. In order to better understand the effect of supply chain inventories on firm performance, three types of inventories: raw materials, work-in-process, and finished goods are separately considered. Analyzing the panel data set of 272 Korean manufacturing firms for the period 1996 to 2012, the following conclusions based on regression methodology has been drawn. After controlling for previous inventory, we find there exists an optimal level of current inventory that maximizes current firm profitability. Furthermore, it is examined whether the external competition level is high using clustering analysis. We find that the effects of supply chain inventories on performance are influenced by the competitive intensity of an industry. The results suggest that while all types of inventories show the non-linear effects on firm performance in the highly competitive market, only finished goods inventory shows significant effects on firm performance in the low competitive market. Our study provides empirical supports for how each type of inventories should be managed and contributes to the extant literature by suggesting managerial implications from a supply-chain perspective perspective for practical engineers and technical professionals.